Handling and pathology reporting guidelines for bladder epithelial neoplasms - recommendations from the Brazilian Society of Pathology / Brazilian Society of Urology / Brazilian Society of Clinical Oncology - Daniel Abensur Athanazio; Luciana Schultz Amorim; Isabela Werneck da Cunha; Fabio Távora; Marcela Santos Cavalcanti; Stephania Martins Bezerra; Emilio Assis; Igor Campos da Silva; Fernando Korkes; Roni Fernandes; Igor Protzner Morbeck; Vinicius Carrera Souza; et al. (BMC, 2024)
Abstract The Brazilian Society of Pathology Guidelines Project aims to provide recommendations for clinicians and pathologists based on the best available scientific evidence. It reviews the currently available and emerging histopathological and molecular aspects of bladder cancer that are necessary for the best patient's management. This paper is a result of a combined effort of the Brazilian Society of Pathology, the Brazilian Society of Urology, and the Brazilian Society of Clinical Oncology to call attention to the essential pre-analytical issues, the required clinical information and specimen handling to allow proper diagnosis, grading, staging and characterization of the molecular aspects of bladder epithelial neoplasms.